Early rhythm-control ablation therapy in preventing AF recurrences: insight from the CHARISMA Registry. (24th May 2021) - Segreti, L; De Simone, A; Schillaci, V; Pandozi, C; Bongiorni, MG; Stabile, G; Arestia, A; Giannotti Santoro, M; Pelargonio, G; Scaglione, M; Rossi, P; Pecora, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: An early and comprehensive rhythm-control therapy emerges as a need to treat AF in an effective way and to improve the ablation outcomes, in terms of arrhythmia-free survival. Purpose: We aimed to investigate the importance of timing of ablation in preventing AF recurrences. Methods: 153 consecutive patients (pts) undergoing AF ablation from the CHARISMA registry at 8 Italian centres were included. Ablations were guided by a novel radiofrequency ablation catheter with local impedance (LI)-sensing capability through a dedicated algorithm (DirectSense, Boston Scientific). Pts were grouped as early treated (ET) if the procedure was performed within 1 year after the first AF episode and as delayed treated (DT) if admitted for ablation after more than 1 year. The ablation endpoint was PVI as assessed by entrance and exit block. Post-ablation follow-up was scheduled at 3, 6 and 12 months. AF and atrial tachycardia (AT) recurrences were considered as long-term endpoint. Results: Of the 153 pts enrolled (69.9% male, 59 ± 10 years, 61.4% paroxysmal AF, 38.6% persistent AF), 123 (80.4%) met Class I indications, 23 (15%) Class IIa indications and 7 (4.6%) Class IIb indications according to current ESC AF guidelines. The mean time to ablation procedure from the first AF episode was 1034 ± 1483 days. Eighty pts (52.3%) were included in ET group, whereas 73 pts (47.7%) in DT group. No differences were found between AF type in terms of ablation strategy (53.3% of the cases -52 out 94- were classified as ET for paroxysmal AF vs 47.5% of the cases -28 out 59- were ET for persistent AF, p = 0.4346). At the end of the procedures, all PVs had been successfully isolated in all study pts. During a mean follow-up of 366 ± 130 days, 18 pts (11.8%) suffered an AF/AT recurrence after the 90-day blanking period. Recurrences occurred mostly in the DT group compared to the ET one (13 out 73 -17.8%- vs 5 out 80 -6.3%-, p = 0.042) and the time to AT/AF recurrence was longer in the ET group (HR = 0.2876, 95%CI: 0.1029 to 0.8038; p = 0.0181). On multivariate logistic analysis adjusted for baseline confounders, only hypertension (HR = 4.66, 95%CI: 1.5 to 14.48, p = 0.0081) was independently associated with recurrences. An early rhythm-control therapy was associated with a low risk of recurrences beyond the hypertension risk factor, ranging from 2% (no hypertension and an ET ablation therapy) to 30.3% (with hypertension and a DT procedure) (Figure 1). Conclusion: A LI-guided ablation strategy for PVI proved to be safe and effective and resulted in a very high recurrence-free rate. An early rhythm-control therapy in the absence of common risk factors was associated with the lowest rate of recurrences.